Study of the Optical and Structural Properties of Metal-Doped Titanium Dioxide Electrode Prepared by the Sol-Gel Method for Dye-Sensitized Solar Cells - Hadeel D. Hamadalla; Falah H. Ali (Iraqi Journal of Physics)
This study presents a strategy to increase the efficiency of dye-sensitized solar cells (DSSCs) by doping titanium dioxide (TiO2) with different magnesium (Mn) concentrations (1, 3, 5, 7, and 9%) generated by the sol-gel process and effectively employed as a photo-anode (the working electrode) for DSSCs. The Doctor Blade method coated the indium-doped tin oxide (ITO) glass with a thin film layer. X-ray diffraction (XRD) was used to evaluate the characteristics of undoped and manganese-doped TiO2, and the results demonstrate that all of the thin films are anatase. The samples were examined using XRD to assess grain size before and after Mn doping. The spectrum of UV-Vis absorption changes; accordingly, as doping increases, the energy gap decreases. The smallest energy gap's value (2.4 eV) is 7% manganese doping. AFM pictures show the average roughness and root mean square of the weight percentage of films doped with 5%. Field effect scanning electron microscope (FE-SEM) studies show that the particle size of thin films gets smaller as more Mn is added, which happens at least as much as 7% Mn doping. The optimal thickness for TiO2 paste over conductive glass is 15 μm, and the cell's power conversion efficiency increased to 0.604074% with an Imax of 4.965 mA, a Vmax of 0.488 V, and a fill factor (FF) of 68.45954%.